Who owns Haiti? : people, power, and sovereignty - Maguire, Robert E. (Robert Earl), 1948-; Freeman, Scott (Lecturer); Wilentz, Amy (University Press of Florida, 2017)
"Contributors illuminate the role of external actors in Haitian sovereign affairs over the course of the last decade, concurrently discussing how Haitians reinforce their self-determination on economic, political, and cultural levels"--Provided by publisher.